2021
DOI: 10.1556/066.2021.00080
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of sea buckthorn extract in oxidative stability improvement of high oleic sunflower oil

Abstract: Sea buckthorn (Hippophae rhamnoides) with high antioxidant capacity is distributed all over the world, but has never been used as a natural antioxidant in oils to replace synthetic antioxidants. Therefore, this study was performed to investigate the effectiveness of sea buckthorn extract in comparison to a common natural antioxidant rosemary extract and a synthetic antioxidant on retarding lipid oxidation. First the extracts were characterised, and it was found that sea buckthorn extract had higher polyphenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The average IP of the oils from the traditional varieties was 2.6 h, predisposing them to cold cooking or short-term frying, while the 11.8 h of the four HOSO oils refers to the possibility of long-term heat stress. Both values were consistent with the range of 1-4 h, as published in the literature [44][45][46][47]. For comparison, typical IP values in hours are given for palm oil (7)(8)(9)(10)(11)(12), soybean oil (1-7), rapeseed oil (3-5), and olive oil (6)(7)(8)(9)(10)(11), performed at 120 • C [44].…”
Section: Oxidative Stabilitysupporting
confidence: 91%
“…The average IP of the oils from the traditional varieties was 2.6 h, predisposing them to cold cooking or short-term frying, while the 11.8 h of the four HOSO oils refers to the possibility of long-term heat stress. Both values were consistent with the range of 1-4 h, as published in the literature [44][45][46][47]. For comparison, typical IP values in hours are given for palm oil (7)(8)(9)(10)(11)(12), soybean oil (1-7), rapeseed oil (3-5), and olive oil (6)(7)(8)(9)(10)(11), performed at 120 • C [44].…”
Section: Oxidative Stabilitysupporting
confidence: 91%
“…For example, Kita et al (2013) found that the content of anthocyanins in fried potato chips decreased by up to 80% after frying. From another angle, the addition of plant extracts can improve the oxidative stability of oil and reduce the formation of hazardous substances in a certain time (Mardani et al, 2021). However, prolonged high-temperature processing may cause the structure of the phytochemicals in plant extracts to be altered, thereby decreasing their antioxidant activity (Troise et al, 2014).…”
Section: Inhibitory Effects and Influencing Factorsmentioning
confidence: 99%
“…Antioxidants play essential roles in the food industry as they improve the oxidative stability of food products (Akoh, 2017; Mardani et al., 2021). Antioxidants inhibit oxidative routes by a variety of mechanisms, including inactivation of peroxides and other reactive oxygen species, scavenging of free radicals, chelation or sequestration of metal catalysts, and quenching of secondary lipid oxidation products (Akoh, 2017).…”
Section: Introductionmentioning
confidence: 99%